Strategi Komunikasi Pemasaran Digital Agensi Kreasiku Visual dalam Membangun Brand Awareness di Instagram - Atta, Alfan; Ramadiansyah, Sahri Aflah (Badan Penerbit STIEPARI Press, 2026)
This study examines the digital marketing communication strategy implemented by Kreasiku Visual Agency in building brand awareness on Instagram. In the digital era, social media has become the primary channel for companies and creative agencies to establish communication, expand promotional reach, and strengthen brand image. This study uses a qualitative descriptive method to in-depth describe the process of designing, managing, and implementing Kreasiku Visual's digital marketing communication strategy. Data were obtained through observations of social media activities, interviews with internal agency personnel, and documentation of digital content. The results show that an integrated and consistent digital communication strategy plays a significant role in increasing Kreasiku Visual's brand awareness. Through an Integrated Marketing Communication (IMC) approach, the agency is able to effectively coordinate communication elements such as digital advertising, visual content, storytelling, and audience interaction. However, obstacles were also identified such as a lack of consistent uploads, limited resources, and suboptimal use of interactive features. Optimizing content strategy and strengthening visual identity are important steps for Kreasiku Visual in strengthening its brand image and competitiveness in the digital era.